Time is ripe: maturation of metabolomics in chronobiology. (February 2017) - Rhoades, Seth D; Sengupta, Arjun; Weljie, Aalim M
Graphical abstract: Highlights: Metabolism is a nexus of sleep and circadian processes as observed by metabolomics. An overlapping set of metabolites is emerging from sleep and circadian studies. These studies have unique data processing, design and statistical considerations. Validation and increased coverage are required for robust chrono-metabolism markers. Future mechanistic studies will be needed to complement biomarkers. Abstract : Sleep and circadian rhythms studies have recently benefited from metabolomics analyses, uncovering new connections between chronobiology and metabolism. From untargeted mass spectrometry to quantitative nuclear magnetic resonance spectroscopy, a diversity of analytical approaches has been applied for biomarker discovery in the field. In this review we consider advances in the application of metabolomics technologies which have uncovered significant effects of sleep and circadian cycles on several metabolites, namely phosphatidylcholine species, medium-chain carnitines, and aromatic amino acids. Study design and data processing measures essential for detecting rhythmicity in metabolomics data are also discussed. Future developments in these technologies are anticipated vis-à-vis validating early findings, given metabolomics has only recently entered the ring with other systems biology assessments in chronometabolism studies.